Effects of low pH and high TA-N on performance of turbot (Psetta maxima) in recirculating aquaculture systems - Mota, Vasco (2009)
Dissertação de mest., Aquacultura e Pescas, Faculdade de Ciências do Mar e do Ambiente, Universidade do Algarve, 2009 Turbot (Psetta maxima) is an emerging species in aquaculture, with a great expansion potential. Recirculating aquaculture systems (RAS) for this species are being developed in several countries. Under this intensive fish farming conditions stress is frequent. In this report primary, secondary, and tertiary stress responses were studied in turbot (374 ± 4 g) exposed during 59 days to low pH (5.8) alone or in combination with high NH4 +‐N concentration (50 mg. L‐1 NH4 +‐N), plus a control (pH 7.5 and <1 mg. L‐1 NH4 +‐N) in duplicate RAS. At the end of the chronic exposure there were no significant differences in plasma cortisol and glucose levels. Survival was also similar for all groups. However, turbot reared at low pH and high ammonium showed blood acidosis and significantly higher Na+ and Cl‐ plasmatic concentrations. These fish also showed a significantly lower growth rate compared to the control. After the growth trial, turbot were submitted to an acute stressor, where fish were chased with a dip net for 5 min and air exposed for additional 10 min. Blood was collected immediately before the stress induction and after 2 and 24 h. The stress response after 2 h involved activation of the HPI‐axis in a similar way to turbot in all groups, as indicated by the cortisol elevations coupled with higher glucose and lactate levels. An iono‐osmorregulatory misbalance was also observed after 2 h, as demonstrated by higher osmolality, Na+ and Cl‐ concentrations. Acid‐base disturbances were also observed, there was a visible drop of blood pH and HCO3 ‐ concentration. After 24 h, the above parameters for turbot in the control group returned to resting levels. However, fish exposed to a previous chronic stressor still presented altered values for osmolality, ionic, and acid‐base parameters. Turbot exposure to low pH in combination with high ammonium concentration showed disturbances at homeostasis level ...